Cerebral Microstructural and Microvascular Changes in Non-Neuropsychiatric Systemic Lupus Erythematosus: A Study Using Diffusion Kurtosis Imaging and 3D Pseudo-Continuous Arterial Spin Labeling - Wang X; Huang L; Guo W; Tang L; Wu A; Wu P; Zhao X; Lin Q; Yu L (Dove Medical Press, 2023)
Xiaojuan Wang,1,* Lingling Huang,1,* Wenbin Guo,2,* Langlang Tang,1 Aiyu Wu,3 Peng Wu,4 Xiance Zhao,4 Qi Lin,1 Lian Yu3 1Department of Radiology, Longyan First Affiliated Hospital of Fujian Medical University, Longyan, Fujian, 364000, People's Republic of China; 2Department of Pathology, Pingtan Comprehensive Experimental Area Hospital, Fuzhou, Fujian, 350400, People's Republic of China; 3Department of Rheumatology, Longyan First Affiliated Hospital of Fujian Medical University, Longyan, Fujian, 364000, People's Republic of China; 4Philips Healthcare, Shanghai, 200000, People's Republic of China*These authors contributed equally to this workCorrespondence: Qi Lin, Department of Radiology, Longyan First Affiliated Hospital of Fujian Medical University, No. 105, Jiu Yi North Road, Xin Luo District, Longyan City, 364000, People's Republic of China, Tel + 86 13950881931, Email linqii8m@126.com Lian Yu, Department of Rheumatology, Longyan First Affiliated Hospital of Fujian Medical University, No. 105, Jiu Yi North Road, Xin Luo District, Longyan City, 364000, People's Republic of China, Email yulianian@126.comPurpose: The purpose of this study was to observe cerebral microstructure and microcirculation features, as well as changes in white matter (WM) and gray matter (GM) among patients with non-neuropsychiatric systemic lupus erythematosus (non-NPSLE).Methods: We compared 36 female patients with non-NPSLE and 20 age- and gender-matched healthy controls (HCs) who underwent 3.0T MRI imaging with diffusion kurtosis imaging (DKI) and 3D pseudo-continuous Arterial Spin Labeling (pCASL). Mean kurtosis (MK), mean kurtosis tensor (MKT), and cerebral blood flow (CBF) values were obtained from 25 brain regions, including WM and GM. We analyzed the correlation between imaging indicators and clinical data.Results: When compared with HCs, patients with non-NPSLE had reduced MK and MKT values in regional WM, deep GM, and the left frontal lobe cortical GM, and increased CBF in the right parietal lobe WM and right semioval center (SOC). The MK and MKT values were weakly correlated with CBF in some regions, including WM and GM. Complement 3 (C3) and Complement 4 (C4) showed a weak positive correlation with MK and MKT in some regions, including WM and deep GM, while platelet (PLT) was positively correlated with MKT in the left frontal lobe WM; dsDNA antibody was correlated negatively with MK in the right occipital lobe WM; and erythrocyte sedimentation rate (ESR) was correlated negatively with CBF in the left SOC.Conclusion: Our findings revealed the presence of brain microstructural and microvascular abnormalities in non-NPSLE patients, indicating microstructural damage in the cortical GM, which was less commonly reported. We found DKI and pCASL useful in detecting early brain lesions, and MK was a more sensitive and beneficial indicator.Keywords: arterial spin labeling, cerebral blood flow, diffusion kurtosis imaging, gray matter, systemic lupus erythematosus, white matter